HBR's 10 must reads on managing yourself, - Harvard Business Review (HBR's 10 must reads, 2010)
HBR's 10 Must Reads on Managing Yourself will inspire you to:Stay engaged throughout your 50+-year work life. Tap into your deepest values. Solicit candid feedback. Replenish physical and mental energy. Balance work, home, community, and self. Spread positive energy throughout your organization. Rebound from tough times. Decrease distractibility and frenzy. Delegate and develop employees' initiative.